NETRALITAS KPU PROVINSI DKI JAKARTA PADA PENYELENGGARAAN PEMILIHAN GUBERNUR DKI JAKARTA TAHUN 2017 - Zainul Djumadin (Jurnal Ilmu dan Budaya, 2019)
Implementation of Regional Head General Election (Pemilukada) that meets the quality of democracy is very much determined by the organizer of Pemilukada (Regional KPU), as the institution responsible for the implementation of the General Election itself. Legitimacy of Pemilukada can be damaged if the institution is in favor of one or several contestants, planning is not mature, the implementation of electoral stages is not neat, discriminatory voter registration, vote counting is not transparent and so on, it all depends on the credibility and integrity of the Pemilukada organizer. However, in practice conflicts of interest also often occur, when a KPU member has an emotional bond and / or debt with one candidate pair who has planted a favor or helped him when registering as a KPU candidate member. So often these alignments arise when the implementation of the General Election is held. From here this study intends to deepen the study of the neutrality of the DKI Jakarta Provincial KPU in the Implementation of the 2017 Governor Election, with the main issue of the neutrality of the DKI Jakarta Provincial KPU in the Implementation of the 2017 Governor Election. This research uses a qualitative research method, in which data sources are obtained by using literature and in-depth interviews.